African Swine Fever: Penyakit Emerging yang Mengancam Peternakan Babi di Dunia - Indrawati Sendow; Atik Ratnawati; NLP I Dharmayanti; Muharam Saepulloh (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
African swine fever (ASF) is a highly infectious disease in pigs that caused by the double-stranded DNA virus of the Asfarviridae family. The disease is characterized by haemorrhages in the ears, back and legs. This virus causes death in pigs and has a large economic impact. However, ASF is not a zoonotic disease, hence it has no an impact on human health. This paper  will discuss about ASF disease, route of transmision, how to diagnose, and handling of ASF. This disease has spread throughout Asia in a relatively short time in 2019, and this exotic disease has been reported entering Indonesia at the end of 2019. There is no effective prevention and control of the disease. Several vaccines have been developed but are still considered ineffective while commercial vaccines are not yet available. Safety and effectiveness of vaccines are still being considered because ASF virus is very unique and different from other DNA viruses,. Therefore, prevention of ASF infection should be done by conducting strict biosecurity, applying regulations on the movement of pigs and pig products to the region or country.